2023
DOI: 10.1101/2023.03.01.530454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IgG4 serum levels are not elevated in cases of Post-COVID syndrome

Abstract: Recently, unexpectedly high virus-specific IgG4 levels were reported after more than two mRNA vaccinations. Class switch towards IgG4 occurs after long-term antigen exposure, downregulates immune responses and is associated with several autoimmune diseases.Here, we examined differences in antigen-specific IgG subtypes in serum samples from 64 Post-COVID patients and an equally sized cohort of convalescent controls.In both cohorts, the relative amounts of spike protein-specific IgG subtypes were comparable. IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…While recent reports have found unexpectedly high virus-specific IgG4 levels after more than two mRNA vaccinations [49,50], another report has observed low total IgG4 levels in 64 PCC samples with small but significant difference for the spike protein receptorbinding domain that may contribute to chronic inflammation [51]. As the authors of those recent publications have not clarified the disease severity in the reported patients, our novel finding of significantly upregulated IgG4 levels in patients with deep phenotyping of particularly severe disease course with concomitant ME/CFS may serve as groundwork for future functional studies.…”
Section: Potential Immune Dysregulation As a Risk Factor For Pediatri...mentioning
confidence: 91%
“…While recent reports have found unexpectedly high virus-specific IgG4 levels after more than two mRNA vaccinations [49,50], another report has observed low total IgG4 levels in 64 PCC samples with small but significant difference for the spike protein receptorbinding domain that may contribute to chronic inflammation [51]. As the authors of those recent publications have not clarified the disease severity in the reported patients, our novel finding of significantly upregulated IgG4 levels in patients with deep phenotyping of particularly severe disease course with concomitant ME/CFS may serve as groundwork for future functional studies.…”
Section: Potential Immune Dysregulation As a Risk Factor For Pediatri...mentioning
confidence: 91%
“…Consequently, examining the distribution patterns of IgG subtypes holds promise for uncovering nuanced insights into SARS-CoV-2 immune response, and potentially elucidating connections between clinical risk factors, serological markers, and post-acute sequelae. However, as yet there are few reports on IgG subtypes in relation to PCC and this is a gap that warrants comprehensive investigation ( 16 , 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%